Analysis of internal logistic cost on exports of peruvian coffee in the period 2015 - 2019 - Caballero Nonalaya, Estefani Wendy (2021)
The objective of the research was to analyse the main components of internal logistics costs that are shown in the process of Peruvian coffee exports in the period 2015-2019. This study used various government sources, document review, and extraction of information systems. To do this we take into account 6 departments with greater coffee production, connected with three logistics corridors that have as a starting point the production areas and reach the export channels of Callao and Paita. Also, using the information gathered from the logistics performance index, a brief internal transport comparison was made between Peru and Colombia. As a result, the logistic cost of both countries is higher than 14.1% (Latin American average), taking into account that in both countries the only internal logistic component in which they coincide is transportation. It is concluded that national transportation hurts impact on logistics costs, since these are affected in the final price of coffee and the profitability of the Peruvian farmer.